Method of biometric measurement of glenoid cavities: Study scannographic 200 glenoid cavities. Issue 5 (31st May 2019) - Menu, G; Boyer, E; El Ramadan, S; Torrens, C; Obert, L; Aubry, S
Introduction: Evaluating the size and morphology of the glenoid can help customize the prosthetic treatment. But there are few large workforces in studies examining CT scan measures the glenoid. We report an analysis of the dimensions of the glenoid. Materials and Methods: 100 consecutive chests CT performed 15 months including two non-pathological glenoid cavities were analyzed by three operators. There were 54 women and 46 men with a mean age of 64.8 years (20-92). Each glenoid was evaluated in 2D reconstruction, on several sections, on the CARESTREAM software. We made our measurements only on healthy or slightly worn glenoid. The largest vertical axis, the largest horizontal axis, the surface of the glenoid, and the circle tangent to the inferior pole of the glenoid were analyzed. The depth and the bone stock of the glenoid were measured in 9 points of the circle, divided into four quadrants, corresponding to the screw positions of a metaglenoid. Results: For each patient, both glenoid cavities were symmetrical compared to the measured criteria. Measurements on 200 glenoids found themselves: the largest vertical axis reached 38.5 mm (25-51), the largest horizontal axis: 27.9 mm (20-56) and the area circle tangential to the lower pole of the glenoid 624.5mm² diameter (324-983). The analytical study to classify the glenoid cavities by size in 3 families: small (area of the circle = 420mm²), medium (525mm²) and large (685mm²). The average size of the patients was de166.9 (147-192). The dimensions of the glenoid were correlated with the size of the patient for 3 families. The most representative measure of the size of the glenoid was the largest horizontal axis, also corresponding to the diameter of the circle inscribed in the glenoid. We measured the depth of the glenoid at the frequent passage of screws during the placement of glenoid implants. Above 10.7 mm, there is an increased risk of suprascapular nerve injury in the posterosuperior dial of the circle inscribed in the glenoid. We compared intra and inter individual measures between the 3 operators. The measurement method is reliable and reproducible with an average difference of 2.7 mm over all the measurements compared. Discussion: These results are similar to those already present in the literature. The large number of patients included in this cohort associated with the reliability and reproducibility of the measurements allow us to adapt this method to the preoperative planning of the placement of glenoid implants in prostheses. The main limitation remains the two-dimensional character of our study.